This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 12. Related Rates P. K. Lamm 10/07/11 (22:33) p. 1 / 7 Lecture Notes: 12. Related Rates These classnotes are intended to be supplementary to the textbook and are necessarily limited by the time allotted for classes. For full and precise statements of definitions and theorems, as well as material covering other topics and examples, please consult the textbook. Example 1.1: A particle moves around the unit circle as a function of time. At time t = 3, x = 3 / 5 m, y = 4 / 5 m, and x = 2 m/s. What is y (3)? 1. Draw a picture and label the variables. 2. What is wanted and what is given? Answer: Wanted: y (3) Given: x (3) = 3 / 5, y (3) = 4 / 5, x (3) = 2. Since we’re given x (3) but we want y (3), it makes sense to ask the following: 3. Are x ( t ) and y ( t ) related? If so, how? Answer: If x ( t ) and y ( t ) are unrelated, then we should be able to pick them as we wish. In fact, however, the point ( x ( t ) ,y ( t )) must always lie on the unit circle. This means that the two functions are related and that we must always have x 2 ( t ) + y 2 ( t ) = 1 , for all t. (1) Note that the relationship between x ( t ) and y ( t ) holds for all time , not just for the time t = 3. This will become important in the next step: 4. Differentiate the relationship equation (1) with respect to the independent variable ( t ). The reason for this step is we have already related the functions x ( t ) and y ( t ), but what we really need to do is relate the rates x ( t ) and y ( t ). d dt x 2 ( t ) + y 2 ( t ) = 1 1 12. Related Rates P. K. Lamm 10/07/11 (22:33) p. 2 / 7 or, since x 2 ( t ) = ( x ( t )) 2 , a power of a function of t (with a similar statement for y 2 ( t )) we must use the Chain Rule to differentiate: 2 x ( t ) x ( t ) + 2 y ( t ) y ( t ) = 0 This last equation holds for all t , but we actually only need information about y ( t ) at t = 3: 5. Evaluate the rate equation at the time of interest ( t = 3 ): 2 x (3) x (3) + 2 y (3) y (3) = 0 6. Solve for the quantity ( y (3) ) of interest: 2 y (3) y (3) = 2 x (3) x (3) y (3) = x (3) x (3) y (3) , = (3 / 5) · 2...
View
Full
Document
 Fall '10
 KIHYUNHYUN
 Calculus, Pythagorean Theorem, P. K. Lamm

Click to edit the document details